Impact of Social Support and Reciprocity on Consumer Well-Being in Virtual Medical Communities - Jyh-Jeng Wu PhD; Che-Hui Lien PhD; Tien Wang PhD; Tzu-Wei Lin MBA (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2023)
This study pursues a better understanding of consumer well-being in online medical cosmetics communities by investigating the antecedents of well-being and moderating influence of community norms. A total valid sample of 484 respondents was collected from 2 popular medical cosmetics discussion platforms. A partial least squares analysis was used to validate the research model. Emotional support, informational support, and sense of belonging were important predictors of well-being. Among these 3 antecedents, emotional support showed the strongest influence on consumer well-being. Sense of belonging was significantly and positively influenced by emotional support and reciprocity, and hence plays a pivotal role in mediating the effects of emotional support and reciprocity on well-being. However, informational support does not appear to significantly influence sense of belonging. Members’ compliance with community norms positively moderates the influence of sense of belonging on well-being. This study contributes to the literature on realizing members’ social behaviors specifically in virtual medical cosmetics communities and provides insights for the management of online communities.